1994
DOI: 10.1038/ng0694supp-246
|View full text |Cite
|
Sign up to set email alerts
|

The 1993–94 Généthon human genetic linkage map

Abstract: In 1992, we described a second-generation genetic linkage map of the human genome. Using 1,267 new microsatellite markers, we now present a new genetic linkage map containing a total of 2,066 (AC)n short tandem repeats, 60% of which show a heterozygosity of over 0.7. Statistical linkage analysis based on the genotyping of eight large CEPH families placed these markers in the 23 linkage groups. The map includes 1,266 intervals and spans a total distance of 3690 centiMorgans (cM). A total of 1,041 markers could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
918
3
9

Year Published

1995
1995
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,709 publications
(957 citation statements)
references
References 26 publications
27
918
3
9
Order By: Relevance
“…Allelic loss was assessed at the markers flanking hMSH2 on chromosome 2p16 and hMLH1 on 3p21 using microsatellite repeats as close together as possible to detect small regions of deletion (Gyapay et al, 1994;Tomlinson et al, 1996). Representative autoradiographs of the gels used for scoring in this study are shown in Figure 4.…”
Section: Results Of Microsatellite Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Allelic loss was assessed at the markers flanking hMSH2 on chromosome 2p16 and hMLH1 on 3p21 using microsatellite repeats as close together as possible to detect small regions of deletion (Gyapay et al, 1994;Tomlinson et al, 1996). Representative autoradiographs of the gels used for scoring in this study are shown in Figure 4.…”
Section: Results Of Microsatellite Analysismentioning
confidence: 99%
“…Three dinucleotide microsatellite repeats on chromosome 2p16 (D2S123, D2S391, D2S119) and 3p21 (D3S1612, D3S1611, D3S1561) were used. Primer sequences were taken from the 1993-94 Genethon human genetic linkage map (Gyapay et al, 1994).…”
Section: Microsatellite Analysis At Hmsh2 and Hmlh1 Locimentioning
confidence: 99%
“…Patient information and DNA extraction Paired primary breast tumours and normal samples were obtained from patients at the S. Giovanni Vecchio Hospital, Turin, Italy as previously outlined (Merlo et al, 1994 2p (sFJS14) 6q (sAVA3) Ilp (D1lS2071) 14q (D14S826) 16q (D16S303) 18q ( Other microsatellites Details of other primer sequences previously reported are: D17S925, D17S926, D17S849 (Gyapay et al, 1994); D17S625 (Utah 269) (Gerken et al, 1995);cCII7.713 (Stack et al, 1994); TP53 (Jones and Nakamura, 1992); cCI17-571, D17S1147 (Stack et al, 1995 A similar LOH study was conducted using resectable staged, non-small-cell lung tumours, the results of which are shown in Table III …”
Section: Methodsmentioning
confidence: 99%
“…Since the early 1990s, developments in the human genome project 9,10 have made it possible to employ more systematic approaches to the search for susceptibility genes in complex diseases. 11 In multiple sclerosis, six whole genome screens for linkage have now been performed.…”
Section: Introductionmentioning
confidence: 99%